(untitled) (International Journal of Scientific Trends, 2024)
Cellulose nanocrystals were obtained by hydrolysis process from waste paper industry. The result of Fourier transform infrared spectroscopy (FTIR) for nanocellulose showed that no new chemical bonds were formed during the preparation of nanocellulose. The results of X-ray diffraction showed that the crystallinity of the macules produced in the treated and untreated paper industry was 66% and 73.8%, respectively. The results of nanocellulose revealed a natural needle-like fiber with a length of 300 nm to 600 nm, a diameter of 10 nm to 30 nm, and an aspect ratio in the range of 10 to 60. It was found that the obtained nanocellulose particles improve the physical properties of paper sheets, in particular, tear resistance strength, traction and burst indices. The maximum increase in mechanical properties was achieved with the addition of 6.0% nanocellulose.